Adverse childhood experiences and the substance use behaviors of Latinx youth. (1st October 2021) - Villamil Grest, Carolina; Cederbaum, Julie A.; Lee, Jungeun Olivia; Unger, Jennifer B.
Highlights: Findings evidence the predictive nature of ACEs on Latinx youth substance use. ACEs exert a unique impact on alcohol use, after controlling for cultural factors. Cultural strengths can be eroded by the negative impact of ACEs. Abstract: Purpose: Adverse childhood experiences (ACEs) are associated with substance use, how cultural factors influence this association for Latinx youth is unknown. This study uses longitudinal data to examine associations of cultural factors, ACEs and substance use among Latinx young adults. Methods: Latinx youth ( N = 1179) completed surveys from a longitudinal study at seven assessment points from 2005 to 2016; ACEs was assessed when participants were on average 21.6 and substance use 23.9 years. ACEs measured psychological, physical, and sexual abuse, parental violence, divorce, substance use, mental illness, and incarceration. A three-stage hierarchical ordinary least squares (alcohol use) and negative binomial regression models (problematic alcohol, marijuana and tobacco use) were estimated to evaluate the role of cultural factors (acculturation, enculturation and ethnic identity) and ACEs in shaping substance use behaviors. Results: Controlling for cultural variables, ACEs sum ( B = 0.03, p = .01), maltreatment ( B = 0.16, p < .01), and household ( B = 0.12, p = .03) subdomains predicted alcohol use. One additional increase in maltreatment (IRR=1.23, 95 % CI: 1.00, 1.53) predicted 23 % higher count of problematic alcohol use. Maltreatment (IRR=1.50, 95 % CI: 1.05, 2.13) and household (IRR=1.66, 95 % CI: 1.18, 2.32) subdomains predicted increased counts of marijuana use. Four or more ACEs predicted increased counts of tobacco use (IRR=1.49, 95 % CI: 1.08, 2.06) among Latinx young adults. Conclusions: Results suggest a predictive relationship between ACEs, and alcohol, marijuana and tobacco use, after accounting for cultural factors. Beyond acculturation, enculturation and ethnic identity, findings identify ACEs as a salient predictor of substance use among Latinx young adults.